Niewystarczalność Prawa w wychowaniu według Listu do Galatów - Stasiak, Sławomir (Verbum Vitae, 2012)
St. Paul in his Letter to the Galatians does not criticise all the stipulations of Law. He pays attention only to the works required by the Law and rejects them as insufficient for the proper education of the Christians. Considering this insufficiency of the Law, St. Paul claims that it was based on inheritance and not on the promise given to Abraham (3:16). The Law was limited and served as an educator (3:24-25). So, the purpose and the way of education is the Gospel of Christ (1:6-9) which the Apostle received directly from the Resurrected (1:12) and then presented to the most influential people in Jerusalem, thus acquiring their acceptance (2:1-2). Incarnation of the Son of God (4:4-5), crucifixion and death of Jesus (2:19-21, 3:1, 6:14) and the descent of the Holy Spirit (4:6) are the three essential elements of Paul’s Gospel. Another crucial constituent of education according to the Letter to the Galatians is faith (2:16), and more precisely, the obedience of faith (3:1-5), which in no case can be connected with the stipulations of Law.